A Report On World English Variety – Tok Pisin - Selmina Rumawak (Publikasi Indonesia, 2025)
Tok Pisin, one of the official languages of Papua New Guinea, has evolved into a lingua franca spoken by over six million people in the country. This study aims to analyze the history, sociolinguistic context, as well as the morphological and syntactic features of Tok Pisin, one of the official languages of Papua New Guinea. The research is qualitative descriptive in nature. The population includes Tok Pisin speakers in Papua New Guinea, with a sample of 15 Papua New Guinean students in Melbourne selected using purposive sampling. Data were collected through literature analysis and surveys. Data analysis was conducted thematically with triangulation. The findings highlight the significant role of Tok Pisin as a lingua franca connecting more than 800 language groups in Papua New Guinea, despite the diverse opinions among its speakers. Morphologically, the language exhibits strong English influence through the use of affixes